Transformasi Digital dalam Manajemen Perkantoran Pendidikan: Sebuah Kajian Literatur - Ahyani, Edi; Dhuhani, Elfridawati Mai (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: This study aims to investigate the impact of digital transformation in educational office management through a comprehensive literature review. Digital transformation, which is mainly triggered by the development of information technology, has reshaped the educational landscape by introducing innovative solutions to improve the efficiency and effectiveness of office management in educational institutions. This literature review involves a review of the evolution of information technology in the education sector and an in-depth understanding of the application of management information systems. In this context, we explore the positive impact of digital transformation on operational efficiency and productivity of educational institutions. In addition, this study identifies and analyzes challenges and barriers that educational institutions may face during the digital transformation process, including data security issues and ethical dilemmas. By detailing best practices and success cases from the relevant literature, the research provides in-depth insights into how educational institutions can take maximum advantage of digital transformation in the context of office management. The results of this literature review are expected to provide valuable guidance for education practitioners and researchers who are interested in optimizing the use of information technology in improving the efficiency and effectiveness of office management in educational institutions.Key Words: Digital Transformation, Education Office Management. Abstrak: Penelitian ini bertujuan untuk menyelidiki dampak transformasi digital dalam manajemen perkantoran pendidikan melalui tinjauan literatur yang komprehensif. Transformasi digital, yang terutama dipicu oleh perkembangan teknologi informasi, telah membentuk kembali lanskap pendidikan dengan memperkenalkan solusi inovatif untuk meningkatkan efisiensi dan efektivitas manajemen perkantoran di lembaga-lembaga pendidikan. Kajian literatur ini melibatkan peninjauan terhadap evolusi teknologi informasi di sektor pendidikan dan pemahaman mendalam tentang penerapan sistem informasi manajemen. Dalam konteks ini, kami mengeksplorasi dampak positif transformasi digital terhadap efisiensi operasional dan produktivitas lembaga pendidikan. Selain itu, kajian ini mengidentifikasi serta menganalisis tantangan dan hambatan yang mungkin dihadapi lembaga pendidikan selama proses transformasi digital, termasuk isu keamanan data dan dilema etika. Dengan merinci praktik terbaik dan kasus sukses dari literatur yang relevan, penelitian ini memberikan wawasan mendalam tentang bagaimana lembaga pendidikan dapat mengambil manfaat maksimal dari transformasi digital dalam konteks manajemen perkantoran. Hasil dari kajian literatur ini diharapkan dapat memberikan panduan berharga bagi praktisi pendidikan dan peneliti yang tertarik untuk mengoptimalkan pemanfaatan teknologi informasi dalam meningkatkan efisiensi dan efektivitas manajemen perkantoran di lembagalembaga pendidikan.Kata Kunci: Transformasi Digital, Management Perkantoran Pendidikan. Pendahuluan